Preventive effect of Terminalia bellirica (Gaertn.) Roxb. extract on mice infected with Salmonella Typhimurium - Kong, Qinghui; Shang, Zhenda; Liu, Yao; Fakhar-e-Alam Kulyar, Muhammad; Suo-lang, Sizhu; Xu, Yefen; Tan, Zhankun; Li, Jiakui; Liu, Suozhu (Frontiers in Cellular and Infection Microbiology, 2023)
Terminalia bellirica (Gaertn.) Roxb. (TB) is a traditional herbal combination used in Chinese medicine for the treatment of a broad range of diseases. In this study, thirty KM mice were randomly divided into control (N), infection group (NS), and the TB protection group (HS). Based on its digestive feature, intestinal physical barrier, immunological barrier and gut microbiota effects in vivo on challenged with S.typhimurium mice were investigated after oral administration of 600 mg/kg b.wt of TB for 13 days. The results show that the extract could improve the level of serum immunoglobulins (IgA and IgG), decrease the intestinal cytokine secretion to relieve intestinal cytokine storm, reinforce the intestinal biochemical barrier function by elevating the sIgA expression, and strengthen the intestinal physical barrier function. Simultaneously, based on the V3–V4 region of the 16S rRNA analyzed, the results of the taxonomic structure of the intestinal microbiota demonstrated that the TB prevention effect transformed the key phylotypes of the gut microbiota in S. Typhimurium-challenged mice and promoted the multiplication of beneficial bacteria. Furthermore, the abundance of Firmicutes and Deferribacteres increased, while that of Bacteroidetes and Actinobacteria decreased. At the genus level, the abundance of Ruminococcus and Oscillospira was substantially enhanced, while the other dominant genera showed no significant change between the vehicle control groups and the TB prevention groups. In summary, these results provide evidence that the administration of TB extract can prevent S. Typhimurium infection by alleviating the intestinal physical and immunological barriers and normalizing the gut microbiota, highlighting a promising application in clinical treatment. Thus, our results provide new insights into the biological functions of TB for the preventive effect of intestinal inflammation.